Studi Kriminologi Penyelesaian Kekerasan Dalam Rumah Tangga di Kota Kupang - Lamber Missa (Universitas Syiah Kuala, 2013)
ABSTRACT: Violence behavior might happen in every household. The violence is not on its criteria but more on the reasons for committing it. This paper explores (1) Phenomena of cases of domestic violence in Kupang (2) phenomena of the violence viewed from criminology aspect. This research applies by applying analytical method by applying juridical empirical research. This research starts by exploring and assessing laws either criminology factors in secondary data and will be then followed by empirical factors by gathering primary data. From its character, this is descriptive analytical research. The data applied are primary data and secondary data. To analyze it, quantitative analysis is then used. The findings show that based on criminology aspect, the violence committed in Kupang is due to economy, jealous and drinking factors. In solving it always used custom approach and also the law. It is recommended that the violence should be monitored by society and it is not only internal problem but also legal one and the family should prevent it from committed. Criminology Study on Settling Domestic Violence Case in Kupang Municipality